Wide-Aperture Backscattering Detector (BSD-A) for The High-Resolution Fourier Diffractometer - C., V. Hai; Balagurov, A.M.; Bogdzel, A.A.; Bodnarchuk, V.I.; Daulbaev, O.; Drozdov, V.A.; Zhuravlev, V.V.; Kirilov, A.S.; Kulikov, S.A.; Kurilkin, A.K.; Kazliakouskaya, А.А.; Milkov, V.M.; et al. (Nuclear Science and Technology, 2026)
: The high-resolution Fourier diffractometer (HRFD) has been in routine operation since 1994 at the long-pulse neutron source, the IBR-2 reactor, in Dubna. Its fast Fourier chopper provides probably the best compromise between very high resolution in reciprocal space (Δd/d ≈ 0.001) and the intensity. For further improving intensity of TOF-diffraction pattern, a wide-aperture ring backscattering detector (BSD) has been developed on the basis of ZnS(Ag)/6LiF scintillator. BSD is designed in the form of 6 concentric rings, each of which is subdivided into 12 identical parts. The main parameters of the detector are the following: range of scattering angles is 2θ = (133 - 175) degrees, covered solid angle is Ωd ≈ 2.0 sr, average percentage absorption efficiency gets closer to 85%, geometrical contribution to resolution function does not exceed Δd/d = 0.0005. In the report the concept of the detector is described and its data acquisition system is presented. The start of operation of the detector at the HRFD is scheduled for 2024.